FORMATION OF PROPER BREATHING SKILLS IN STUDENTS DURING VOCAL PERFORMANCE TRAINING SESSIONS - Hamroqulov , Naimdjon (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article extensively discusses the importance of breath control as one of the fundamental elements of vocal technique for students, as well as its influence on voice quality and intonation. It also analyzes the pedagogical methods, exercises, and the organization of systematic training sessions used to develop breathing skills during lessons. The study further examines issues related to expanding students’ vocal abilities, enhancing their creative thinking, and improving musical expressiveness through the development of proper breathing techniques.